Responsibly strategizing with the metaverse: Business implications and DEI opportunities and challenges - Marabelli, Marco; Newell, Sue (The journal of strategic information systems, 2023)
•The metaverse has strategic implications for organizations.•The metaverse involves DEI opportunities and challenges.•It is important, for IS scholarship, to join the interdisciplinary conversation about the metaverse.•Institutionalism represents an effective umbrella theory to develop novel theorizing on the metaverse. This viewpoint article aims to lay out the foundations for IS research on the strategic implications as well as diversity, equity, and inclusion (DEI) opportunities and challenges of the metaverse – a sociotechnical system providing users with an immersive, synchronous 3D experience of (virtual) reality through interoperable platforms and sensor devices. We first examine the metaverse’s technologies and its underlying business models, which hold immense strategic implications for organizations and industries, and might require rethinking the future of work. As with most emerging technologies able to generate, collect, and process user data, the metaverse comes at a price; leveraging the metaverse strategically will require ethical and DEI considerations. After examining all these aspects of the metaverse, we reflect on ways IS scholarship engaged in strategizing can advance theoretical and practical knowledge by generating novel research questions and outlining a research agenda. Our contribution is twofold: first, we analyze the metaverse using a sociotechnical lens, thereby setting the ground for future studies of the phenomenon. Second, we identify specific strategic implications as well as DEI opportunities and challenges associated with the metaverse, and discuss how scholarship versed in IS strategizing can contribute to addressing them, both theoretically and empirically.